Laccase Application for Upgrading of Lignocellulose Fibers - Maja Vaukner Gabrič (University of Zagreb, Faculty of Forestry and Wood Technology, 2015)
Laccases have the ability to oxidize both phenolic and trough mediators non-phenolic lignin related compounds. When reacting on lignin, they can display both ligninolytic and polymerizing (cross-inking) abilities, which makes them very useful for their application in industries based on lignocellulose material. Most of the published papers and applications of laccase and laccase-mediator systems on lignocellulose material relate to the pulp, paper and textile industry. Recent research has been done in terms of laccase assisted biografting of phenols and other compounds on wood surface and use of laccase for adhesion enhancement in fiberboard production. They can be introduced to wood technology as environmentally friendly enzymes. The paper reviews the application of laccases in industries based on lignocellulose material and discusses the future outlook and development in the above mentioned fields.